Ecosistema naranja: elementos en las artes escénicas en Carora, Venezuela (Gestión y Gerencia, 2020)
The Orange Economy relates the creative, cultural, economic and social sector worldwide, this sector is transformed into an opportunity focused on talent, creations exchange and give life to completely innovative products, full of intellectual and expressive value. The research focuses on the orange ecosystem at the local level of the city, including dance and theater. The objectives are to determine the offer, describe the demand and identify the institutions related to the creative sector. Quantitative research, with a descriptive, cross-sectional methodology and a field design was undertaken; the technique of data collection was through a survey and an observation guide. The results were analyzed in SPSS and Excel statistical programs expressed in pie charts and tables. It is concluded that the city has organizations and academic institutions of recognized tradition dedicated to the mentioned arts, and high level organizers of cultural activities. Government participation and the private sector are recommended to form an Orange Ecosystem in the City
Keywords: Orange economy; orange ecosystem; supply; demand; institutions